The effect of attitude towards behaviour, local wisdom culture, whistleblowing intention on fraud prevention - Marota, Rochman; Rosnidah, Ida; Juhaida Johari, Razana (Edelweiss Applied Science and Technology, 2024)
The potential state losses due to corruption cases that occurred in Indonesia from 2017-2021 tend to increase very significantly. This research aims to explore the relationship between attitude and whistleblowing intentions which is also strengthened by local wisdom as well as the role of whistleblowing intention and its influence on fraud prevention. The research method used in this research is a quantitative approach using SEM PLS. The research results show that attitude towards behavior influences whistleblowing intention and whistleblowing intention influences fraud prevention. Meanwhile, the role of local wisdom is not proven to increase the whistleblower’s attitude to act to report fraud violations. It is hoped that the results of this research can be used as a consideration in making decisions related to the phenomenon of whistleblowing and fraud in the world of practice and will also become material to be scrutinized in determining applicable regulatory policies to improve local traditions.